APPLICATION OF TECHNOLOGY BASED LEARNING MEDIA IN IMPROVING STUDENTS READING COMPREHENSION AT THE TENTH GRADE OF SMK N 1 BOTOMUZOI IN 2023/2024 - Halawa, Anugrah Abadi Jaya; Laoli, Adieli; Riswan Zega; Telaumbanua, Yasminar Amaerita (Esteem Journal of English Education Study Programme, 2025)
The process of comprehending a text in which the reader, the text, and the context interact is known as reading comprehension. Reading comprehension makes it easier for someone to understand what they are reading. The purpose of this study was to determine whether using technology-based learning resources may improve the reading comprehension of tenth-grade students at SMK Negeri 1 Botomuzoi in 2023–2024. Observation sheet exercises, tests, and field notes were used to gather data for this study, which aims to determine how technology-based learning materials might be used to enhance students' reading comprehension. Classroom Action Research (CAR) was the methodology employed in this study. Based on the findings of the first cycle, which had an average of 45% of students who responded to a test question, researchers completed their study in two cycles. Because the first cycle's value fell short of the 70% Minimum Competency Criteria, the researcher proceeded to the second cycle once the first cycle was finished.  The second cycle's average score for students who responded to the test questions was 85%. in order for students' reading comprehension to be enhanced through the use of technology-based learning resource.